Importance des Parametres Hydrodynamiques dans la Repartition Spatiale des Sediments Superficiels des Plages de Limbe (Sud-Ouest Cameroun) - Arnaud, Kouekam Kengap; Gustave, Fowe Kwetche Paul; Fulbert, Togue Kamga; Romain, Ngueguim Jules; Ginette, Dingong Atoukoh Thérèse (European Scientific Journal, ESJ, 2019)
This paper contributes to the determination of the importance of the hydrodynamic parameters acting on the Limbe coast (South-West Cameroon) using the particle size analysis of surface sediments of the beaches. In achieving this objective, two sediment sampling campaigns on the beaches of Batoke and Debundscha respectively were carried out along 8 radials perpendicular to the shoreline. For each radial, three samples were taken respectively at the three geomorphological units. From the beach, a total of 24 samples were taken for particle size analysis and sedimentometry in the laboratory. The main results obtained show that the superficial sediments of the Batoke beaches are mainly characterized by sediments of the class of fine sands. They are very well classified and their distribution is almost symmetrical towards the end. On the other hand, the beach of Debundscha is characterized by a predominance of medium sands sediments. Also, they are very well classified and their distribution is asymmetric towards coarse. From a hydrodynamic point of view, this granulometric distribution of sediments shows that Batoke and Debundscha beaches are mostly transported by constant energy swells with very low currents. Compared to the Batoke site, Debundscha has more severe swell conditions. The estimated tidal range (RTR = 3.01) which is greater than 1 during the study period indicates that tidal currents dominate wave-generated currents. Thus, this indicates that the tide may be the only responsible parameter for the spatial distribution of sediment on the two beaches. La présente étude contribue à la détermination de l’importance des paramètres hydrodynamiques agissant sur la côte de Limbe (Sud-ouest Cameroun) à l'aide de l'analyse granulométrique des sédiments superficiels des plages. Pour atteindre cet objectif, deux campagnes de prélèvements de sédiments respectivement sur les plages de Batoke et Debundscha ont été effectuées le long de 8 radiales perpendiculaires à la ligne de rivage, pour chaque radiale, trois prélèvements ont été effectués respectivement au niveau des trois unités géomorphologiques de la plage soit au total 24 échantillons ont été prélevés pour des analyses granulométriques et sédimentométries au laboratoire. Les principaux résultats obtenus nous montrent que les sédiments superficiels des plages de Batoke sont majoritairement caractérisés par des sédiments de la classe des sables fins, très bien classés et dont la distribution est presque symétrique vers les fins tandis que la plage de Debundscha est caractérisée par une prédominance des sédiments de la classe des sables moyens, très bien classés et dont la distribution est asymétrique vers les grossiers. Du point de vu hydrodynamique, cette répartition granulométrique des sédiments montre que les plages de Batoke et Debundscha sont majoritairement transportés par les houles à énergie constante dont les courants sont très faibles mais par rapport au site de Batoké, Debundscha présente des conditions de houle plus importante. Le paramètre de marnage évalué (RTR=3,01) supérieur à 1 durant la période d'étude montre que les courants de marée dominent sur les courants générés par la houle traduisant ainsi que la marée pourrait être le paramètre majoritairement responsable de la répartition spatiale des sédiments sur ces deux plages.